The Influence of Company Reputation and Service Quality on Decisions to Purchase Professional Recruitment Services (Case Study of The Headhunter Industry) - Fernando Fernando; Dimas Angga Negoro; Bambang Purwoko Kusumo Bintoro (Jurnal Scientia, 2024)
This study aims to analyze the effect of company reputation and service quality on purchasing decisions for headhunter services. This study is to determine the basis for consumer considerations in choosing a headhunter company, and for headhunter companies this research can be a reference in maintaining relationships with their customers. There are 3 hypotheses tested, and this study uses quantitative methods by conducting surveys. The sampling method is using probability sampling with a sample size of 115 respondents based on the hair formula. As for analyzing the data of this study using multiple linear regression analysis methods.The company's reputation and service quality both influence the decision to purchase headhunter services, with the main factor having higher relevance being the service quality variable.